Towards a more accurate measure of foreign bank entry and its impact on domestic banking performance: The case of China - Xu, Ying (Journal of Banking & Finance, 2011)
This paper examines the impact of foreign bank entry on China’s banking performance. An innovation in this study is that it constructs a spatially disaggregated measure of foreign bank presence, employing location data of foreign bank branches. Using this measure, the study examines the relationship between foreign bank presence and domestic banking performance in China. The results show that the spatially disaggregated measure not only improves the assessment of the impact of foreign bank presence but also resolves unexplained discrepancies found in existing empirical studies contingent on aggregate measures. Importantly, the study provides strong empirical evidence that foreign bank entry is supportive of a more competitive and efficient banking industry in China.